Analysis of spontaneous emission in a 1D photonic crystal with effective resonator model - Rudziński, Adam; Szczepański, Paweł (Photonics Letters of Poland, 2010)
This letter discusses the application of effective resonator model as a tool for analysis of spontaneous emission in one-dimensional photonic crystals built of a finite number of layers and with arbitrary defects of layer's width or refractive index. It is pointed out that quantities defined in the model allow analyzing the properties of the structure without calculating field distributions. Full Text: PDF References E. Yablonovitch,"Inhibited Spontaneous Emission in Solid-State Physics and Electronics", Phys. Rev. Lett. 58, 2059 (1987)[CrossRef] S. John,"Strong localization of photons in certain disordered dielectric superlattices", Phys. Rev. Lett. 58, 2486 (1987)[CrossRef] M. Bugajski, J. Muszalski, T. Ochalski, J. Kątcki, B. Mroziewicz,"Resonant Cavity Enhanced Photonic Devices", Acta Phys. Pol. A 101, 105 (2002) P. Szczepański,"Semiclassical theory of multimode operation of a distributed feedback laser", IEEE J. Quantum Electron. 24, 1248 (1988)[CrossRef] W. Nakwaski,"Principles of VCSEL designing", Opto-Electron. Rev. 16, 18 (2008)[CrossRef] N.A. Jackman,"Multilayer optical filters with random errors", Bell Labs Tech. J. 3, 112 (1998)[CrossRef] Q. Zhu, Y. Zhang,"Defect modes and wavelength tuning of one-dimensional photonic crystal with lithium niobate", Optik 120, 195 (2009)[CrossRef] A.S. Sánchez, P. Halevi,"Spontaneous emission in one-dimensional photonic crystals", Phys. Rev. E 72, 056609 (2005)[CrossRef] C.K. Carniglia, L. Mandel,"Quantization of Evanescent Electromagnetic Waves", Phys. Rev. D 3, 280 (1971)[CrossRef] H. Rigneault, S. Monneret,"Modal analysis of spontaneous emission in a planar microcavity", Phys. Rev. A 54, 2356 (1996)[CrossRef] W. Żakowicz,"Spontaneous emission by atoms in simple environments", Acta Phys. Pol. A 101, 119 (2002). P. Yeh, A. Yariv, C.-S. Hong,"Electromagnetic propagation in periodic stratified media. I. General theory", J. Opt. Soc. Am. 67, 423 (1977)[CrossRef] P. Yeh, Optical waves in layered media (New York, John Wiley & Sons 1988). Rudziński, A. Tyszka-Zawadzka, P. Szczepański,"Simple model of the density of states in 1D photonic crystal ", Proc. SPIE 5950, 59501A (2005)[CrossRef] A. Rudziński, A. Tyszka-Zawadzka, P. Szczepański,"Spatial and frequency domain effects of defects in 1D photonic crystal", Opt. Quant. Electron. 39, 501 (2007)[CrossRef] A. Rudziński,"Analytic expressions for electromagnetic field envelopes in 1D photonic crystal", Acta Phys. Pol. A 111, 323 (2007) A. Rudziński,"Some mathematical properties of effective resonator model of 1D dielectric multilayer structure", Acta Phys. Pol. A 115, 660 (2009) A. Rudziński, P. Szczepański,"Calculation of atomic spontaneous emission rate in 1D finite photonic crystal with defects", Cent. Eur. J. Phys., in press; [CrossRef]